Modulating Excitonic Recombination Effects through One‐Step Synthesis of Perovskite Nanoparticles for Light‐Emitting Diodes. Issue 19 (12th September 2017) - Kulkarni, Sneha A.; Muduli, Subas; Xing, Guichuan; Yantara, Natalia; Li, Mingjie; Chen, Shi; Sum, Tze Chien; Mathews, Nripan; White, Tim J.; Mhaisalkar, Subodh G.
Abstract: The primary advantages of halide perovskites for light‐emitting diodes (LEDs) are solution processability, direct band gap, good charge‐carrier diffusion lengths, low trap density, and reasonable carrier mobility. The luminescence in 3 D halide perovskite thin films originates from free electron‐hole bimolecular recombination. However, the slow bimolecular recombination rate is a fundamental performance limitation. Perovskite nanoparticles could result in improved performance but processability and cumbersome synthetic procedures remain challenges. Herein, these constraints are overcome by tailoring the 3 D perovskite as a near monodisperse nanoparticle film prepared through a one‐step in situ deposition method. Replacing methyl ammonium bromide (CH3 NH3 Br, MABr) partially by octyl ammonium bromide [CH3 (CH2 )7 NH3 Br, OABr] in defined mole ratios in the perovskite precursor proved crucial for the nanoparticle formation. Films consisting of the in situ formed nanoparticles displayed signatures associated with excitonic recombination, rather than that of bimolecular recombination associated with 3 D perovskites. This transition was accompanied by enhanced photoluminescence quantum yield (PLQY≈20.5 % vs. 3.40 %). Perovskite LEDs fabricated from the nanoparticle films exhibit a one order of magnitude improvement in current efficiency and doubling in luminance efficiency. The material processing systematics derived from this study provides the means to control perovskite morphologies through the selection and mixing of appropriate additives. Abstract : I′m so excitonic ! A process to form MAPbBr3 perovskite nanoparticle (NP) films formation directly on substrate surface through one‐step in situ deposition method is described, avoiding the pitfalls of forming thin films from preformed NPs. Partial substitution of the MABr with OABr regulates the NP growth rate. The NPs film is highly luminescent (photoluminescence quantum yield=20.4 %) and displays an excitonic emission signature.